IMPLIMINTASI PERILAKU KEPEMIMPINAN PT VENTURA BERBASIS PROMOSI JALUR KARIR - Mukrodi Mukrodi (Sekolah Menengah Kejuruan (SMK) Pustek, 2019)
Human resources are assets in an organization or company, so that with these resources, what the company wants to achieve can be realized well and realistically. So in this case the author intends to conduct research related to leadership and career. Leadership behavior in the business world is a driving factor in the business world in order to control the running of an organization or company, so that with this behavior it is hoped that the company can run well. With this research, I as the author have the aim of finding out how much leadership behavior is related to career promotion, so that with good leader behavior, healthy promotions can be created, with healthy promotions it will be possible to produce a healthy company. This research uses a descriptive qualitative approach by collecting data through in-depth interviews with employees and related parties in the company. Content analysis is used to identify patterns of leadership behavior that influence the career path-based promotion process. Apart from that, concepts from leadership theory and career development are also used as a guide in analyzing data and factors for promotion. The attitude of a good leader can play an important role in advancing the Company, so that the Company's activities can be successful and successful. Leadership behavior has not been fully carried out in accordance with applicable theories and rules, while the career path factors that dominate at PT Ventura are the channeling career path combined with strong knowledge and experience so that this career path is dominated by many in the company.